On the Narrative of “Things” in Tobacco Road - Zhang, Shuyao (Pacific International Journal, 2024)
American writer E.，Erskine Caldwell’ s novel Tobacco Road depicts the ignorant, backward and miserable lives of poor whites in the American South, revealing the ills of the southern society during that era. In the novel, the boundaries between people and objects are blurred, and people are objectified as victims of land and social oppression. Furthermore, things have an active power in the novel, driving the plot and carrying historical and spatial significance at the same time. The dilapidated houses and deserted farmland symbolise the end of an era and foreshadow social change. By analysing the “things” in the work, we can gain a deeper understanding of the tensions between peasants and natural resources, as well as the injustices in the social structure. The perspective of the object narrative also provides us with profound social and cultural insights into the economic exploitation and cultural oppression suffered by the poor sharecroppers in the South under the imperial rule.